2022
DOI: 10.1186/s12884-021-04342-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intrauterine insemination in women with endometrioma-associated subfertility: analysis using propensity score matching

Abstract: Background Intrauterine insemination (IUI) treatment is recommended in subfertile women with AFS/ASRM stage I/II endometriosis. However, the efficacy of IUI in women with ovarian endometriomas with tubal patency is uncertain. We explored the efficacy of IUI for the treatment of endometrioma-associated subfertility. Methods We performed a retrospective matched cohort study using propensity matching (PSM) analysis. Subfertile couples undergoing IUI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Per-cycle and cumulative pregnancy rates were not significantly different compared to women with unexplained infertility and this rate was not different with associated ovarian stimulation. The same study concluded that IUI with endometrioma was more likely to convert to IVF, however the authors chose to collect and report the CPR rather than the LBR [29]. These findings confirm the ESHRE suggestion that IUI with ovarian stimulation may be suitable for women with endometrioma and no other identified infertility factors [2].…”
Section: Intrauterine Insemination In Women With Endometriosismentioning
confidence: 61%
“…Per-cycle and cumulative pregnancy rates were not significantly different compared to women with unexplained infertility and this rate was not different with associated ovarian stimulation. The same study concluded that IUI with endometrioma was more likely to convert to IVF, however the authors chose to collect and report the CPR rather than the LBR [29]. These findings confirm the ESHRE suggestion that IUI with ovarian stimulation may be suitable for women with endometrioma and no other identified infertility factors [2].…”
Section: Intrauterine Insemination In Women With Endometriosismentioning
confidence: 61%